Irrational Use of Medicines-A Summary of Key Concepts - Richard Ofori-Asenso; Akosua Adom Agyeman (MDPI AG, 2016)
Medicines play an integral part of healthcare delivery. However, they are expensive commodities and account for a significant proportion of overall health expenditure in most countries. Irrational use of medicines is a major challenge facing many health systems across the world. Such practices are likely to lead to poor health delivery that may put patients at risk and result in wastage of scarce resources that could have been used to tackle other pressing health needs. The concept of "rational use of medicine" can at times be confusing and not easily appreciated by patients, healthcare providers, policy makers, or the public, all of whom need to collaborate effectively to address this challenge. In this article, we summarize basic concepts such as rational medicine use, good prescribing and dispensing, and explore some of the factors that contribute to irrational use of medicines as well as potential impacts of such practices. This article has been written with the intention of offering a clear, concise, and easy to understand explanation of basic medicine use concepts for health professionals, patients, policy makers, and the public.